2020
DOI: 10.25259/ijms_29_2020
|View full text |Cite
|
Sign up to set email alerts
|

Role of poly (ADP) ribose polymerase-1 inhibition by nicotinamide as a possible additive treatment to modulate host immune response and prevention of cytokine storm in COVID-19

Abstract: COVID-19 is rapidly spreading contagious disease spreading across the world. Patients at risk are elderly people and those with comorbidity. Early studies done on Chinese patients who suggest cytokine storm to be responsible for lung injury. We need to understand the mechanism of modulating such robust response of immunity and resultant cytokine storm. We suggest nicotinamide, a potential poly ADP ribose polymerase (PARP) inhibitor, as a supportive treatment for the prevention of cytokine storm from injuring t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Furthermore, niacin might also decrease neutrophil infiltration, while exhibiting a prolonged anti-inflammatory effect during ventilator-induced lung injury. However, niacin exacerbated hypoxemia regardless of the neutrophil infiltration decrease, suggesting a different cause of hypoxemia, independent of neutrophil decline [ 144 , 145 ], which requires further investigation. In addition, high efficiency of vitamin B3 (niacin or nicotinamide) in preventing lung tissue damage was confirmed in several animal models with bleomycin- and LPS-induced lung injury [ 146 , 147 , 148 ].…”
Section: Infection Treatment and Immunomodulatory Effectsmentioning
confidence: 99%
“…Furthermore, niacin might also decrease neutrophil infiltration, while exhibiting a prolonged anti-inflammatory effect during ventilator-induced lung injury. However, niacin exacerbated hypoxemia regardless of the neutrophil infiltration decrease, suggesting a different cause of hypoxemia, independent of neutrophil decline [ 144 , 145 ], which requires further investigation. In addition, high efficiency of vitamin B3 (niacin or nicotinamide) in preventing lung tissue damage was confirmed in several animal models with bleomycin- and LPS-induced lung injury [ 146 , 147 , 148 ].…”
Section: Infection Treatment and Immunomodulatory Effectsmentioning
confidence: 99%
“…PARP 1 inhibition will most likely prevent cell death due to NAD + and ATP depletion. PARP 1 inhibition has been suggested using NAM [ 4 ] or CVL218 (Mefuparib) [ 3 ]. This latter compound inhibits SARS viral replication with an IC 50 of 5.12 µM, and IL-6 production by activated peripheral blood mononuclear cells [ 3 ].…”
Section: Potential Therapies Of Covid-19mentioning
confidence: 99%
“…There are some excellent reviews on the subject (17,40). Here, we focus on the compound stenoparib, pro-inflammatory NF-kB-triggered cytokine storm that can damage host organs (44). It has also been suggested that PARP inhibitors enhance the degradation of the host type I interferon receptor (IFN-1R), which would also have a modulatory effect on the host inflammatory response (45).…”
Section: Discussionmentioning
confidence: 99%